FLIPPED CLASSROOM MODEL IN ENGLISH LANGUAGE TEACHING: IMPLEMENTATION DESIGN, LEARNING OUTCOMES, AND PEDAGOGICAL IMPLICATIONS - Helminsyah Helminsyah; Nurul Zikri Filina; Muhammad Zulhairi Bin Zubairi (SENSEI RESEARCH CENTER, 2026)
In the usual classroom the teacher explains and then gives homework, so the time in the class is used only for explanation. In the flipped classroom it is the opposite, the students watch the video at home and in the class they practice. This article discusses the implementation and the outcomes of the flipped classroom model in English language teaching. The method used is literature review from many journals. The result shows that the flipped classroom can make the students more active and they have more time to speak and to write in the class. But there are also problems, for example the students do not watch the video, the internet is not good, and the video is too long. Therefore the teacher must make the video short and must check whether the students have watched it or not.